2002
DOI: 10.1046/j.1524-4725.2002.02071.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Port-Wine Stain Birthmarks Using the 1.5-msec Pulsed Dye Laser at High Fluences in Conjunction with Cryogen Spray Cooling

Abstract: background. The majority of port-wine stain (PWS) patients treated with the pulsed dye laser (PDL) do not achieve complete blanching. Safe administration of higher fluences has been proposed as a means of improving treatment efficacy. objective. To determine the safety and efficacy of PWS treatment with the 1.5-msec PDL at high fluences in conjunction with cryogen spray cooling. methods. Twenty PWS patients were treated with the PDL in combination with cryogen spray cooling utilizing a 7 or 10 mm spot size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…PWSs improved significantly, often dramatically, following treatment with the long pulseduration PDL. Our results agree with Kelly et al [14], who showed similar rates of clearance using the same type of laser and an average of 3.3 treatments per patient. Further increasing the pulse duration may allow treatment of larger vessels still, since evidence suggests that pulsedurations ranging from 0.45-20 milliseconds would be optimal for clearing PWSs [9,15], with the optimal pulseduration probably varying somewhat as a function of PWS vessel depth and diameter.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…PWSs improved significantly, often dramatically, following treatment with the long pulseduration PDL. Our results agree with Kelly et al [14], who showed similar rates of clearance using the same type of laser and an average of 3.3 treatments per patient. Further increasing the pulse duration may allow treatment of larger vessels still, since evidence suggests that pulsedurations ranging from 0.45-20 milliseconds would be optimal for clearing PWSs [9,15], with the optimal pulseduration probably varying somewhat as a function of PWS vessel depth and diameter.…”
Section: Discussionsupporting
confidence: 93%
“…We report on the treatment of a large number of previously untreated PWSs. In addition, to having a longer pulse duration than previous generation PDLs, newer PDLs utilize surface cooling that protects the epidermis during treatment, resulting in decreased pain and increased efficacy by enabling the delivery of higher treatment fluences [10][11][12][13][14]. In this study, we further our initial observations of increased efficacy of the 1.5-millisecond pulse-duration PDL utilizing a dynamic cooling device (DCD), for treating PWSs.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Current clinical studies give valuable information of the outcome of the therapy, [29][30][31][32][33] but lack information on the degree of purpura, histologic analysis, and insight into the mechanism of vascular damage. Additionally, most of these clinical studies limit the fluences used to 10 J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The novel method of achieving selective epidermal protection with ''dynamic'' or cryogen spray cooling (CSC) is well established and in current use for laser treatment of selected dermatoses [1][2][3][4][5][6][7][8]. However, while CSC can protect the epidermis from non-specific thermal damage, the cryogen film that forms on the skin surface may pose a potential problem of laser light attenuation due to optical scattering.…”
Section: Introductionmentioning
confidence: 99%